INTERNALISASI KARAKTER TAUHID PADA ANAK USIA DINI - Darnawati (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The character of monotheism is a collection of values that are manifested in attitudes and behaviors based on the oneness of Allah. Children of a Muslim are expected to have the character of monotheism because since childhood they are educated in Muslim families that are full of Islamic values. There are several attempts to internalize the character of tawhid in a child, including: 1) proclaiming the call to prayer and iqomah in the child's ear, 2) teaching tauhid sentences to children, 3) educating with compassion and 4) getting used to dhikr and doing prayer also chants the sentence thoyyibah.